Pengaruh Digital Transformation Pada Corporate Risk-Taking - Muhammad Ananda Putra; Rahmat Setyawan (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study analyzed the impact of digital transformation (DT) on corporate risk-taking, which is proxied by the standard deviation of RoA in the last 3 years. This study also examined the moderation effect of high operating leverage on digital transformation (DT) relationships on bank corporate risk-taking. This study employs a quantitative methodology and a panel data model. This study examined 43 banks listed on the Indonesian Stock Exchange between 2018 and 2021, observing a total of 172 firm years. This study utilizes secondary data from annual reports and company financial reports. This study shows that digital transformation decreased corporate risk-taking. High operating leverage also succeeds to moderate the relationship between digital transformation on bank corporate risk-taking. The results of this study show consistency with previous research that shows the relationship of digital transformation to corporate risk-taking has a positive relationship. Keywords: Digital Transformation, Corporate Risk-Taking, Banks